Quality of polyunsaturated fatty acids in Nile tilapias (Oreochromis niloticus) fed with vitamin E supplementation - Navarro, Rodrigo Diana; Silva Pereira Navarro, Fernanda Keley; Ribeiro Filho, Oswaldo Pinto; Ferreira, Walter Motta; Pereira, Marcelo Maia [UNESP]; Seixas Filho, Jose Teixeira (Elsevier B.V., 2012)
Freshwater fish are an important source of protein, but they also contain other highly nutritive components such as fats. Polyunsaturated fatty acids (PUFAs) are essential for normal growth, development and reproduction of vertebrates. The antioxidant role of vitamin E in cell membranes prevents fatty acid and cholesterol oxidation, thereby promoting PUFA and subcellular particle stabilization. The effects of vitamin E supplementation on the quality of Nile tilapia (Oreochromis niloticus) carcass were investigated. The experiments were carried out in an experimental laboratory over 106 d. After sex reversal, 400 early juvenile O. niloticus were tested in a completely randomized experiment with 5 treatments (4 repetitions each), consisting of vitamin E monophosphate supplementation at 0, 50, 100, 150 or 200 mg/kg of a base diet. Treatment diets contained equal amounts of protein and energy. Tilapias supplemented with vitamin E contained arachidonic acid (20:4 omega-6; AA) which participates in inflammatory response. Nile tilapia carcasses that received vitamin E at 100 and 150 mg/kg diet had improved carcass quality by increasing the PUFA:SFA ratio and had the highest levels of polyunsaturated fatty acids from the omega-3 (linolenic acid; 18:3 omega-3) and omega-6 (linoleic acid; 18:2 omega-6) series. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Fish nutrition; Fatty acids; Carcass quality; Antioxidant